INTERACTIVE WEBSITE-BASED SALES INFORMATION SYSTEM FOR THE UNFORMAL FASHION BRAND USING MIDTRANS - Muhammad Nurdiansyah; Sri Nuryani Pujiastuti; Rahma Hanum; Nava Gia Ginasta (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
Developments in the fashion industry are driving businesses to leverage digital technology to improve sales effectiveness and the customer experience. This study aims to design a prototype of a website-based sales information system for the Unformal brand, integrating the Midtrans payment gateway and product customization features. The study employed a qualitative descriptive approach through observation, documentation, and the distribution of questionnaires to 41 respondents as the basis for system requirements analysis. The website prototype was designed using Figma based on the results of STP and SWOT analyses. The results showed that 51% of respondents were interested in using the product customization feature, 63% believed that digital payment integration simplifies transactions, and 78% were interested in promotional programs. The resulting prototype includes the Register, Login, Home, Shop, Custom, Checkout, and Payment pages. This system design is expected to serve as a reference for developing a more integrated sales website and supporting the digitization of business processes for the Unformal brand.